The comparison of health literacy and lifestyle among retired and homemaker older adults' women - Anahita Khodabakhshi-Kolaee (Mashhad University of Medical Sciences, 2016)
Background and objective: The diseases during old age have an enormous impact on women elderly and their families. The previous study indicated that health literacy and lifestyle play a crucial role in prevention of diseases in elderly. Therefore, the aim of current study is to compare the health literacy and lifestyle among retired and homemaker older adults' women. Methods: This study is a descriptive comparative research. The 80 retired women and 80 homemakers were chosen through purposive sampling and sample random sampling respectively in Tehran in 2015. Then, they equalized in aspect of age, education, and economic family status with retired older adults' women. The measuring instruments are Health- Promoting Lifestyle Profile (HELLA) and Health Literacy for Iranian Adults (HPLP II). Data was analyzed utilizing t independent and spss20. Results: The results showed that there is the significant difference between the lifestyle (t=-6.46, df=158, p=0.001) and health literacy (t=-6.59, df= 158, p= 0.001) and the subscales of these variables among retired women and housewives (p